1989
DOI: 10.1073/pnas.86.11.4220
|View full text |Cite
|
Sign up to set email alerts
|

Mouse/human chimeric monoclonal antibody in man: kinetics and immune response.

Abstract: A mouse/human chimeric monoclonal antibody (mAb) composed of the variable regions of murine 17-4A mAb and the constant regions of human IgG-1K immunoglobulin was administered to 10 patients with metastatic colon cancer. Four patients received single infusions of 10 mg (n = 2) or 40 mg (n = 2). Six patients received three infusions of 10 mg (n = 3) or 40 mg (n = 3) at 2-week intervals. The pharmacokinetics were similar at both dose levels and at the second and third infusions. The plasma disappearance curves we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
132
0
1

Year Published

1993
1993
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(137 citation statements)
references
References 20 publications
4
132
0
1
Order By: Relevance
“…Chimeric antibodies have shown a considerable variation in immunogenicity. 14 The human engineered anti-TNFa antibody CDP571 has previously been shown to induce only low concentrations of an IgM type anti-idiotype response with a weak response in IgG. 7 This is in keeping with the pharmacokinetic data showing a long half-life.…”
Section: Discussionmentioning
confidence: 56%
“…Chimeric antibodies have shown a considerable variation in immunogenicity. 14 The human engineered anti-TNFa antibody CDP571 has previously been shown to induce only low concentrations of an IgM type anti-idiotype response with a weak response in IgG. 7 This is in keeping with the pharmacokinetic data showing a long half-life.…”
Section: Discussionmentioning
confidence: 56%
“…The immune response to cM-T412 was assessed by a double-antigen radiometric assay, as previously described (24,29), with serum samples obtained prior to treatment and at 7, 14, and 28 days, and at 2, 4, and 6 months postinfusion. The assay utilized murine M-T412-coated beads and '251-labeled chimeric M-T412 as the radioactive probe.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated the lower immunogenicity of a chimeric MAb (versus an intact murine MAb) in tumor therapy (24 …”
mentioning
confidence: 99%
“…Development of host antibody responses directed against the therapeutic MAb had previously raised concerns about the long-term usefulness of murine MAb (27,28). To overcome this problem, chimeric MAb that exhibit lower immunogenecity compared with the parent murine MAb have been developed (29). We have previously reported on the use of a chimeric anti-CD4 MAb, cM-T412, in a phase I trial, in patients with refractory RA (30,31).…”
mentioning
confidence: 99%